The 'Evo-Demo' Implications of Condition-Dependent Mortality. (December 2017) - Ronget, Victor; Garratt, Michael; Lemaître, Jean-François; Gaillard, Jean-Michel
Abstract : Animals in the wild die from a variety of different mortality sources, including predation, disease, and starvation. Different mortality sources selectively remove individuals with different body condition in different ways, and this variation in the condition dependence of mortality has evolutionary and demographic implications. Subsequent population dynamics are influenced by the strength of condition-dependent mortality during specific periods, with population growth impacted in different ways in short- versus long-lived species. The evolution of lifespan is strongly influenced by condition-dependent mortality, with strikingly different outcomes expected in senescence rates when the relationship between condition and mortality is altered. A coupling of field and laboratory studies is now required to further reveal the evolutionary implications of condition-dependent mortality. Trends: Mortality in the wild is strongly influenced by individual condition. Mortality from predation versus starvation shows different relationships with body mass. The relative condition dependence of different mortality sources will impact population dynamics and life-history evolution in diverse and even opposing ways. A coupling of field and laboratory studies is now required to understand the evolutionary implications of condition-dependent selection by different mortality sources.